Perinatal results of pregnancy with chorioamnionitis in a third level hospital in Lima, 2016 to 2018 - De la Cruz-Dávila, Carmen Carolina (2020)
Objective: To determine the perinatal outcomes of pregnancies with chorioamnionitis seen in the National Maternal and Perinatal Institute (INMP) during the years 2016 to 2018, as well as determine the length of the hospital stay, use of mechanical ventilation and oxygen therapy and determine morbidity during the years. Material and Methods: Descriptive, transversal and retrospective study. We included newborns of mother with chorioamnionitis at the INMP, born between 2016 - 2018. We selected 361 cases. The information was collected through a data sheet. The SPSS 24.0 program was used in the analysis of the data.  Results: The most frequent were the preterms in 51,0%, the birth weight between 2500-3999g was 49,9%; the most frequent delivery route was cesarean (85,0%). The hospitalization was 41,6% longer than 7 days, the very premature babies required oxygen therapy (58.0%) and moderate preterm babies required assisted ventilation (15.4%). The 70,0% of the newborns had morbidity, as neonatal sepsis (56,2%), hyperbilirubinemia (38,0%), transient tachypnea (24,9%), pneumonia (19,7%), coagulation disorder (19,1%), anemia (17.7%), hyaline membrane disease (15,5%) and hypoglycemia (15,2%) among others. The 7,80%. of the total population died. Conclusion: Chorioamnionitis has a serious impact on newborn, is related with multiple morbidity. The increase in hospital stay (> 7 days) and the use of oxygen therapy and assisted ventilation (> 7days) in the group of premature infants were evidenced